Device-Related Complications and Inappropriate Therapies Among Subcutaneous vs. Transvenous Implantable Defibrillator Recipients: Insight Monaldi Rhythm Registry - Russo, Vincenzo; Rago, Anna; Ruggiero, Vincenzo; Cavaliere, Francesca; Bianchi, Valter; Ammendola, Ernesto; Papa, Andrea Antonio; Tavoletta, Vincenzo; De Vivo, Stefano; Golino, Paolo; D'Onofrio, Antonio; Nigro, Gerardo (Frontiers in Cardiovascular Medicine, 2022)
Introduction: In the context of randomized clinical trials, subcutaneous ICD (S-ICD) was shown to be non-inferior to transvenous (T-ICD) with respect to device-related complications or inappropriate shocks in patients with an indication for defibrillator therapy and not in need of pacing. We aimed at describing clinical features of patients who underwent S-ICD implantation in our clinical practice, as well as the ICD-related complications and the inappropriate therapies among S-ICD versus T-ICD recipients during a long-term follow-up. Material and Methods: All patients underwent implantable cardiac defibrillator (ICD), both S-ICD and TV-ICD, at Monaldi Hospital from 1th January 2015 to 1th January 2019 and followed at our Institution were included in the present analysis. The clinical variables associated to S-ICD implantation were evaluated by logistic regression analyses. We collected the ICD inappropriate therapies, ICD-related complications (including both pulse generator and lead related complications), ICD-related infections, appropriate ICD therapies and overall mortality. Kaplan-Meier (KM) analyses were performed to assess the risk of clinical outcome events between the two subgroups. A time dependent Cox regression analyses were performed to adjust the results. Results: 607 consecutive patients (mean age 53.8 16.8, male 77.8%) with both TV-ICD (n: 290, 47.8%) and S-ICD (n: 317, 52.2%) followed at our center for a median follow-up of 1378 day (IQR. 1016- 2041) were included in the study. At multivariate logistic regression analysis, an independent association between S-ICD implantation and ionic channel disease (OR: 6.01 [2.26- 15.87]; P< 0.0001) and ischemic cardiomyopathy (OR: 0.20 [0.12- 0.35]; P<0.0001) was shown. The KM analysis did not show a significantly different risk of the inappropriate ICD therapies (2.2% vs 2.4%; log rank P= 0.64) between the two subgroups; conversely, showed an increase risk of ICD-related complications (6.2% vs 19%; log rank P= 0.02) and infections (3.4% vs 0.3%; log rank P= 0.02) in TV-ICD group. The adjusted risk for ICD-related complication (OR: 0.07 [0.009-0.55], 0.01) and infections (0.31 [0.12- 0.81], 0.01) was significantly lower among S-ICD patients.